2019
DOI: 10.1044/2018_aja-18-0141
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Competencies in Audiology: A Modified Delphi Study

Abstract: Purpose Counseling practices in audiology play a critical role in helping patients and families understand, accept, and adjust to the dynamic impacts ear-related disorders have on their lives. The purpose of this study was to identify what competencies (i.e., knowledge, skills, and attitudes) are important for audiologists to possess to provide effective counseling in practice. Method A modified Delphi study design was used to survey a panel of 33 profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Although more than 80% of audiologists in the current study indicated that they had received some training in the delivery of emotional support, the two most common barriers to providing emotional support during audiology consultations were feeling under skilled and worry that I may get 'out of my depth', suggesting a need for further training and skill development. A recent international Delphi study identified 64 competency items ( 16knowledge-based, 35 skill-based, and 13 attitudinal items) deemed important for audiologists to possess to provide effective audiologic counselling (Meibos, 2019). Meibos (2019) further demonstrated that audiology training programs do not encompass adequate training on the majority of these items, suggesting that practicing clinical audiologists are under-skilled in many of these areas.…”
Section: Beliefs and Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more than 80% of audiologists in the current study indicated that they had received some training in the delivery of emotional support, the two most common barriers to providing emotional support during audiology consultations were feeling under skilled and worry that I may get 'out of my depth', suggesting a need for further training and skill development. A recent international Delphi study identified 64 competency items ( 16knowledge-based, 35 skill-based, and 13 attitudinal items) deemed important for audiologists to possess to provide effective audiologic counselling (Meibos, 2019). Meibos (2019) further demonstrated that audiology training programs do not encompass adequate training on the majority of these items, suggesting that practicing clinical audiologists are under-skilled in many of these areas.…”
Section: Beliefs and Practicesmentioning
confidence: 99%
“…A recent international Delphi study identified 64 competency items ( 16knowledge-based, 35 skill-based, and 13 attitudinal items) deemed important for audiologists to possess to provide effective audiologic counselling (Meibos, 2019). Meibos (2019) further demonstrated that audiology training programs do not encompass adequate training on the majority of these items, suggesting that practicing clinical audiologists are under-skilled in many of these areas.…”
Section: Beliefs and Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Audiologists play an integral role during the counselling process, which highlights the importance of ensuring that audiologists are well equipped with the appropriate training in audiological rehabilitation (Meibos, Muñoz, & Twohig, 2019 ). Presently, there are five tertiary institutions within South Africa offering the degree at undergraduate and postgraduate levels.…”
Section: Resultsmentioning
confidence: 99%
“…Delphi-studies using a modified version of the method have a great potential, as they are very common in the literature, independent of the research area or focus of the paper (e.g. Meibos et al , 2019; Parratt et al , 2016; Slade et al , 2016; Toma et al , 2019). The Delphi technique in oral form, as an example of the modified method, can be applied to different types of groups, such as electronic groups or people meeting in a face-to-face interaction (Witkin and Altschuld, 1995).…”
Section: Theoretical Backgroundmentioning
confidence: 99%